2009
DOI: 10.1109/tpds.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Parallel Task Graphs on (Almost) Homogeneous Multicluster Platforms

Abstract: Abstract-Applications structured as parallel task graphs exhibit both data and task parallelism, and arise in many domains. Scheduling these applications efficiently on parallel platforms has been a long-standing challenge. In the case of a single homogeneous platform, such as a cluster, results have been obtained both in theory, i.e., guaranteed algorithms, and in practice, i.e., pragmatic heuristics. Due to task parallelism these applications are well suited for execution on distributed platforms that span m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Weaknesses in both HCPA (and thus in CPA) and M-HEFT were identified and remedied in [22], which performs a thorough comparison of both improved algorithms. In the case of a homogeneous multi-cluster platform, an algorithm to schedule a single PTG was recently proposed in [13]. This algorithm is based on a resource allocation algorithm that provides a performance guarantee, but has high computational complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Weaknesses in both HCPA (and thus in CPA) and M-HEFT were identified and remedied in [22], which performs a thorough comparison of both improved algorithms. In the case of a homogeneous multi-cluster platform, an algorithm to schedule a single PTG was recently proposed in [13]. This algorithm is based on a resource allocation algorithm that provides a performance guarantee, but has high computational complexity.…”
Section: Related Workmentioning
confidence: 99%
“…This result was improved in [11], leading to a ∼4.73 performance ratio in the general case. The algorithm proposed in [10] was implemented and compared to HCPA in [12]. It was shown that non-guaranteed algorithms were competitive with the guaranteed one on the average but with tremendously shorter scheduling times.…”
Section: Related Workmentioning
confidence: 99%
“…Note that this inner loop actually corresponds to an interval of iterations of the seminal allocation procedure of CPA, as shown in Figure 1. Each time T CP ≤ T ′ A , the current allocation is stored for each task (lines [11][12][13]. At the end of this procedure, P different allocations are associated with each task in the PTG.…”
Section: B the Bicpa Algorithmmentioning
confidence: 99%
“…Research in this area has not considered such parallel tasks as part of a workflow containing task dependencies. For workflow scheduling, existing solutions restrict the execution of parallel tasks to a single cluster [8] [3]. This is due to the support of high interconnection speed, high bandwidth and low latency networks such as Infiniband [9], and the support of Network File System (NFS) which provides easy and transparent access to data from any of the parallel process.…”
Section: Introductionmentioning
confidence: 99%